IMPROVING CHILDREN’S VOCABULARY BY USING ENGLISH FOR KIDS APPLICATION - Agna Fitri Nadzira; Rasi Yugafiati (PROJECT (Professional Journal of English Education), 2023)
The purpose of the research is to know the result of improving children’s vocabulary by using English for kids application. Nowadays, during the covid-19 pandemic, some students play with gadgets in their daily life. Because of that, the researcher wants to compare a game in smartphones to teach English. It is a reason why the researcher wants to know the impact of English for kid application for the TEYL process. This research only focuses to know about improving children’s vocabulary by the English for Kids application. This research is a qualitative method. An interview and questioner use to collect data. The sample of this study is students of SDN Banyuasih II 2020/2021 in Karawang. In the final activity, the researcher asks the students to mention the new vocabulary which they learn in the English for Kids application. The researcher concludes that the English for Kids application can improve children’s vocabulary a little bit. Keywords:  Children’s Vocabulary; English for Kids Application; Qualitative Method